Nilam Oil Financial Feasibility - Bina Unteawati; Irmayani Noer; M Rofiq (Jurnal Ilmiah ESAI, 2012)
The research is aim to analyze the Nilam financial feasibility on high territory land and low down territory.  Location chose purposively on    Kali Asin, Tanjung Bintang subdistrict, South of Lampung Region and  Tulung Gestang, Kota Agung Timur subdistrict, Tanggamus Region.   The research conducted at September until November  2010.  Respondent sample was 10% of Nilam farmer population.  Financial feasibility analyze by criteria of investment:  NPV (Net Present Value), Net B/C ratio, and IRR (Internal Rate of Return).  Based on analysis, Nilam oil on low down territory performed feasible with NPV Rp15.594.676, Net B/C ratio 2,34, and IRR 82%.   The same result also find on Nilam oil on high territory land.  It’s feasible with NPV  Rp 4.479.803, Net B/C ratio 1,29, and IRR 19%. Keywords: Nilam oil, feasibility, financial